Internalization of The Scientific Ulul Model in Learning Morals and Its Implications on Student Character - Supriadi, Udin; Parhan, Muhamad; Budiyanti, Nurti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This article aims to analyze the internalization process of the Ulul Ilmi model in moral learning as a moral aspect of Islamic teachings. The world of education is now restless in the face of increasingly severe moral degradation. The key to education's success lies in innovative educators' hands in developing appropriate learning models to achieve the expected learning goals. This research design uses an R & D (Research and development) approach. The results of this study indicate that the process of internalizing the Ulul Ilmi model, which is carried out in the moral learning process, can have an impact on changing the character of Ulul Ilmi in students. The pre-test results using the Ulul Ilmi model only obtained a 20-50% range. In contrast, the post-test results showed a presentation with a range of 50-70% of the answers to each item presented in the question instrument. That means there is a significant change that is felt by students when the lecturer applies the Ulul Ilmi model in the classroom. Likewise, with the Ulul Ilmi character in students, the results of the pre-test show a range of 20-50% only. Meanwhile, the post-test results show a percentage ranging from 30-60% of the answers to each item presented in the question instrument. That means there are quite good changes obtained from the results of the internalization process in the classroom. However, the percentage obtained does not indicate the optimal presentation because the internalization process that is carried out takes a long time and is continuous. It is better to try again to get the maximum change results in realizing the Ulul Ilmi character in UPI students.